Induction of Estrus in Postpartum Anestrus Murrah Buffaloes using Chelated Minerals and Ovsynch Protocol - Sahu, Suryakant; Prasad Tiwari, Rajendra; Dubey, Meenu; Tirumala Veera Bramhandra Reddy, Bizzala; Kumar Paikra, Dilip (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A research trial aimed to assess the effect of chelated mineral mixture supplementation and Ovsynch protocol on induction of estrus  was conducted on 120 days postpartum true anestrus Murrah buffaloes. A total of 18 true postpartum acyclic buffaloes selected  were divided into three groups each of 6 animals. Group T1 was treated with chelated mineral mixture Agrimin Forte (50 g/day) and  Garbhov bolus (1 bolus/day) for 15 days. In Group T2, chelated mineral mixture as in T1 plus Ovsynch protocol comprising intramuscular  injections of Buserelin acetate (10 µg), Cloprostenol (500 µg), and Buserelin acetate (10 µg) on days 0, 7 and 9, respectively, were given,  and treated buffaloes were inseminated after detected heat. The control group (C) buffaloes received no treatment. Blood glucose, and  serum macro-micro minerals profile was compared pre- and post-treatment between the groups. Estrus was induced in 66.67% and  83.33% of postpartum anestrus buffaloes, respectively, in T1 and T2 groups with intermediate to intense estrus intensities, as compared  to the untreated control group (33.33%). After supplementation of the mineral mixture (T1), concentrations of blood glucose, calcium,  magnesium, copper, iron, and zinc increased significantly (p≤0.05); however, inorganic phosphorus, cobalt, and selenium levels did  not vary significantly post-treatment. In group T2, a significant increase was observed in the mean concentrations of blood glucose,  copper, and cobalt. From the present study, it can be concluded that supplementation of mineral mixture and application of hormonal  synchronization protocol successfully induced estrus in postpartum acyclic Murrah buffaloes and can be adopted as a potential tool to  alleviate the inherited problems of poorly exhibited estrus.
Keywords: Buffalo; Chelated mineral mixture; Estrus induction; Mineral profile; Ovsynch; Postpartum anestrus